Intercellular and extracellular amino acids of different bloom species in the Mediterranean Sea - Hosny Shimaa; El-Sheekh Mostafa; Labib Wagdy (Oceanological and Hydrobiological Studies)
The presented laboratory experiment was designed to characterize the quantity and compositional variation of algal extracellular amino acids (AAs) that may represent an alternative nutrient source in a natural environment. To resemble algal bloom scenarios, analyses were conducted in mono- and/or co-cultures of the bloom-forming species Skeletonema costatum, Scrippsiella trochoidea, Ulva fasciata, and Corallina officinalis during their active growth phase. The study revealed that S. costatum exhibited higher production of the dominant AAs than S. trochoidea. Alanine, lysine, and threonine acids are the dominant amino acids in S. costatum and S. trochoidea filtrates, which may play a role in mucus formation during mucosal phytoplankton blooms with negative ecological effects. On the other hand, aspartic, glutamine, alanine, and leucine acids are the dominant amino acids in macroalgae. In co-culture experiments, U. fasciata shows strong and rapid allelopathic activity against these two potentially harmful species. The AA production offers an advantage to species with the capacity to absorb them to form blooms. Thus, anthropogenic inorganic nutrient inputs may be less important for the development of algal blooms in coastal waters. A major difference that distinguishes this work from others is the use of specific multi-taxa cultures of phytoplankton and macroalgae. The study represents a new research effort in Alexandria waters.